Potential role of cancer stem cells as biomarkers and therapeutic targets in cervical cancer. Issue 2 (8th November 2018) - Sudhalkar, Niyati; Rathod, Nidul P.; Mathews, Ashwathi; Chopra, Supriya; Sriram, Harshini; Shrivastava, Shyam K.; Goda, Jayant S.
Abstract: Background: Eradicating cancer stem cells (CSCs) that are termed as the "beating heart" of various malignant tumors, including cervical cancer, holds great importance in cancer therapeutics. CSCs not only confer chemo‐radio resistance but also play an important role in tumor metastasis and thereby pose a potential barrier for the cure of cervical cancer. Cervical cancer, a common malignancy among females, is associated with high morbidity and mortality rates, and the study on CSCs residing in the niche is promising. Recent findings: Biomarker approach to screen the cervical CSCs has gained impetus since the past decade. Progress in identification and characterization of the stem cell biomarkers has led to many insights. For the diagnostic purpose, several biomarkers like viral (HPV16), stem cell markers, transcription factors (viz, SOX2, OCT 4, and c‐Myc), and CSC surface markers (viz, ALDH1 and CD44) have been identified. The research so far has been directed to study the CSC stemness and demonstrates various gene expression signatures in cervical CSCs. Such studies hold a potential to improve diagnostic accuracy and predict therapeutic response and clinical outcome in patients. Conclusions: Stem cell biomarkers have been validated and their therapeutic targets are being developed as "strategies to improve therapeutic ratio in personalized medicine." This review gives a brief overview of the cervical CSC biomarkers, their current and future diagnostic, prognostic, and therapeutic potential.